A comparison of copper and acid site zeolites for the production of nitric oxide for biomedical applications. Issue 12 (7th March 2017) - Russell, Samantha E.; González Carballo, Juan María; Orellana-Tavra, Claudia; Fairen-Jimenez, David; Morris, Russell E.
Abstract : Copper-exchanged and acidic zeolites are shown to produce nitric oxide (NO) from a nitrite source in biologically active (nanomolar) concentrations. Abstract : Copper-exchanged and acidic zeolites are shown to produce nitric oxide (NO) from a nitrite source in biologically active (nanomolar) concentrations. Four zeolites were studied; mordenite, ferrierite, ZSM-5 and SSZ-13, which had varying pore size, channel systems and Si/Al ratios. ZSM-5 and SSZ-13 produced the highest amounts of NO in both the copper and acid form. The high activity and regeneration of the copper active sites makes them good candidates for long-term NO production. Initial cytotoxicity tests have shown at least one of the copper zeolites (Cu-SSZ-13) to be biocompatible, highlighting the potential usage within biomedical applications.